Analysis of Teacher Knowledge on The Implementation of School or Madrasah Accreditation - Johan Andriesgo; Syarifah Ivonesti; Muhammad Aufa Muis (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study aims to describe the teacher's knowledge of school or madrasa accreditation implementation. The research method that the author uses in this research is descriptive quantitative using documentation, interviews, and observations. The location of this research is in SD/MI in Kuantan Singingi Regency. The study results obtained that teachers' knowledge of school or madrasah accreditation was still minimal, namely around 42% of teachers had moderate knowledge of accreditation, 8% of teachers who had insufficient knowledge of accreditation, 50% of teachers who had high category knowledge.